Avaliação do nível de fadiga de mulheres no puerpério: um estudo de coorte - Silva, Tatiana Camila de Lima Alves da (2022)
The puerperium is a period of vulnerability due to the emotional and physical changes that occur after childbirth and that can influence a woman's quality of life. In this context, the decrease in physical and mental capacity associated with a persistent lack of energy, deficiencies in concentration, decreased rest and sleep time can favor the installation of physical and mental fatigue. The prevalence and incidence of postpartum fatigue has not been studied extensively and is considered an inevitable, temporary and frequently experienced symptom. This study aims to assess the level of fatigue of women in the immediate and late postpartum period and to associate it with sociodemographic and clinical factors. Through a prospective cohort study, 469 women were recruited from a public maternity hospital in the city of Natal-RN, from May to December 2021. The evaluations took place in the immediate postpartum period (between 24-48 hours) and in the puerperium. late (in the 1st and 3rd month after delivery). An evaluation form containing information on sociodemographic, clinical, gynecological-obstetric and newborn data was applied in the first evaluation along with three questionnaires for fatigue assessment: Global Short Form of selfreported global health from the Information System of Measurement of Outcomes by patient (PROMIS-GSF); multidimensional fatigue inventory (MFI) and fatigue pictogram. These data, with the exception of sociodemographic information, were applied one month after the assessment (AV2) and three months after delivery (AV3). Descriptive analysis of variables was used with mean, standard deviation, median, 25th and 75th percentiles, absolute and relative frequencies. Repeated measures ANOVA was used to compare the results of the three fatigue assessments. The multivariate model was adjusted for independent variables with significance ≤ 0.20 in the bivariate analysis and considering the clinical relevance for the occurrence of the outcome. The most prevalent age group was 26 to 34 years old, 59.5% completed elementary school, 47.6% had a salary income of up to one minimum wage and 76.1% reported having a partner. In obstetric information, 70.6% were multiparous with a median gestational age of 38 weeks, 60.5% had vaginal delivery, 95.7% breastfed after delivery and 80.2% breastfed in past pregnancies. The fatigue assessment in the three assessments showed a significant difference in the PROMIS-GSF (p < 0.01), general fatigue domains, physical fatigue and reduced motivation of the MFI (p < 0.01) and the fatigue pictogram (p < 0.01). 0.01). In AV3, the PROMIS-GSF showed an association between fatigue and preterm births (RR = 1.18; 95%CI: 1.02–1.37); absence of a support network (RR = 1.14; 95%CI: 1.02–1.27); poor breastfeeding performance (RR = 1.16; 95%CI: 1.03–1.31) and higher body mass index (BMI), (RR = 1.01; 95%CI: 1.00–1.01). From the analysis of the results of this study, it was possible to observe the presence of fatigue in the immediate postpartum period and its increase over three months postpartum. Prematurity, absence of a support network, poor performance in breastfeeding and higher BMI were factors associated with the persistence of fatigue in the late postpartum period.